2011
DOI: 10.1111/j.1865-1682.2010.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Risks Associated with Commodity Trade: Transmission of Viral Haemorrhagic Septicaemia Virus (VHSV) to Rainbow Trout Fry from VHSV-Carrying Tissue-Homogenates

Abstract: Movements of commodity fish present a potential risk of transferring pathogens. Within a study to estimate the risk from imported rainbow trout Oncorhynchus mykiss carcases, fry were exposed to tissue homogenates from market size rainbow trout infected experimentally with viral haemorrhagic septicaemia (VHS) by waterborne exposure to VHS virus (VHSV, isolate of genotype Ia). Tissues were collected from fish that showed clinical signs and from recent mortalities. Homogenates of (i) internal organs, (ii) brain/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…; Oidtmann et al . ). For instance, freezing‐thawing fish infected with VHSV reduces, but does not abolish, the infectivity of the virus (Arkush et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Oidtmann et al . ). For instance, freezing‐thawing fish infected with VHSV reduces, but does not abolish, the infectivity of the virus (Arkush et al .…”
Section: Discussionmentioning
confidence: 97%
“…A source of the virus could be frozen fish food, bought in Asia, that was used by the farmer as feed in the grayling farm. It is generally admitted that both gutted and round fish used as feed can serve as a possible source of virus transmission to fish reared in farms or to those in the wild (Skall et al 2005;Oidtmann et al 2011). For instance, freezing-thawing fish infected with VHSV reduces, but does not abolish, the infectivity of the virus (Arkush et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen load might therefore be further reduced if frames are decapitated, leaving just the spine and associated flesh. Therefore evisceration cannot be considered to remove all pathogens and all risk (Oidtmann et al, 2011(Oidtmann et al, , 2013.…”
Section: Pathogens Survives Processingmentioning
confidence: 99%
“…However, European strains of VHSV have never been found in salmon and North American VHSV 4 only occasionally (Garver et al, 2013). So although salmon are listed as susceptible to VHS by the OIE (2014), risk of infection at salmon farms from which frames may be sourced is N. VHSV can be transmitted from tissue derived from brains and gills or even fillets (Oidtmann et al, 2011), therefore, if derived from infected fish, frames with the heads on are likely to carry infection (M) but even with decapitation a probability (L) still exists. Since salmon are both highly unlikely to carry VHSV and are resistant should they be exposed (King et al, 2001), it may therefore be concluded that salmon frames, in the quantities used as bait, pose negligible risk of infecting farmed salmon with VHS (Table 5a).…”
Section: Viral Haemorrhagic Septicaemiamentioning
confidence: 99%
“…There are no data on the within-farm prevalence of VHSV in infected farms, and this is likely to be highly variable between farms and over time. However, experimental work indicates that fish surviving infection may carry the virus (Oidtmann et al, 2011a). Even if the prevalence of infection in harvested fish is extremely low, a small consignment is likely to contain at least one infected fish, for example, a consignment of 2000 fish from a population with a prevalence rate of 0.1% will on average contain two infected fish.…”
Section: Entry Assessment (Steps a And B)mentioning
confidence: 99%